Modeling Lahars on a Poorly Eroded Basaltic Shield: Karthala Volcano, Grande Comore Island - Dille, Antoine; Poppe, Sam; Mossoux, Sophie; Soulé, Hamid; Kervyn, Matthieu (Frontiers in Earth Science, 2020)
Lahars impose significant secondary hazards on highly populated volcanic islands by remobilising volcanic ash deposits. Karthala, on Grande Comore Island, is a basaltic shield volcano with sporadic occurrence of ash-forming phreatic eruptions. In 2005, two mildly explosive episodes emplaced tephra blankets on the summit area. Heavy precipitation subsequently triggered the repetitive occurrence of small-volume secondary lahars up to 2012. These lahars impacted the settlements at the foot of Karthala, damaging roads and hundreds of houses, affecting thousands of inhabitants. This study aims at gaining insights into the effectiveness of two simple tools to reproduce the lahars’ extent in this data-poor context. To understand the physical characteristics of the lahars, we first documented the extent and characteristics of the debris deposits at the foot of Karthala volcano and in the ravines that guided the flows. Our observations suggest that the debris was emplaced by small-scale (volumes ≤105 m³), rain-triggered and predominantly low sediment concentration lahars. The spatial extent of the deposits served to calibrate and compare numerical lahar simulations from the widely used volume-limited LaharZ model with results from Q-LavHA, a recent probabilistic flow model originally developed for lava flows. Our comparison demonstrates that LaharZ outperforms Q-LavHA for small-scale lahar simulations. While Q-LavHA has features that mitigate some limitations of LaharZ, such as its ability to simulate flow bifurcations and the transition from constrained to unconstrained flow, it typically underestimates the actual inundated area. Nevertheless, both models show rather poor performance, encountering difficulties in delineating lahar flow paths due to the smooth topography of the volcanic edifice. We therefore also evaluated the potential to increase simulation accuracy by updating a 10-meter resolution Digital Elevation Model (DEM) with channel topography measurements. While this approach led to improved simulation accuracies for both models compared to using un-adapted DEMs, it did not prevent simulations to miss the hazard-prone position of settlements actually affected by the hazard. This study helps inform numerical volcanic flow simulation strategies on young and poorly dissected volcanic edifices, such as basaltic shields, and forms a basis for further developing numerical simulation tools more adapted to these particular environmental settings.